Efficacy of drainage of pleural effusion using small bore pleural catheter and conventional thoracostomy using large bore chest tube: a comparative study - Krishnakumar, Easwaramangalath Venugopal; Anas, Muhammed; Rennis, Davis Kizhakkepeedika; Thomas, Vadakken Devassy; Vinod, Babu (International Journal of Research in Medical Sciences, 2017)
Background: Pleural effusions commonly occur in patients with advanced cancer and tuberculosis. Pleural aspiration by the conventional tube thoracostomy using large bore chest tube-intercostal drain (ICD) - can often cause discomfort to patients. The aim of this study is to compare the efficacy of drainage of pleural effusions using flexible small bore Pleural Catheter (PC) and ICD. Methods: In this prospective study, 101 patients (age 16-65 years) with pleural effusions were divided into PC (n=60) and ICD (n=41) groups. Responses were evaluated and analyzed statistically. Results: The PC group was equally efficacious as ICD with regard to complete re-expansion of lung. The most common complication in the PC group was block (9/60 i.e. 15%). Difference in the mean number of days on drain in the PC (4.9 days) and ICD group (5.8 days) as well as the mean number of times analgesics administered in the PC (2.85 days) and the ICD group (7.53 days) were statistically significant (p <0.05). Similarly, the complications such as surgical emphysema, haemorrhage, desaturation and hypotension were high in the conventional group when compared to that of PC group (p <0.05). Conclusions: Flexible small bore intercostal catheter is a valid and safe option for drainage of pleural effusion when compared to the conventional tube thoracostomy.